The influence of impurities in high temperature polymer electrolyte membrane fuel cells performance - Marta Boaventura (2016)
This work investigates the influence of carbon dioxide and non-reacted methanol, present in the reformate stream obtained via methanol steam reforming, in the performance of high temperature polymer electrolyte membrane fuel cells (HT-PEMFC), operating between 160 C and 180 C. The HT-PEMFC anode was fed with pure hydrogen, hydrogen balanced with carbon dioxide (75%/25% vol.) and synthetic reformate mixture, considering also vaporized methanol solution in the reformate content (up to 10% vol.). The synthetic reformate was feed during cycles of 420 min. The fuel cell was characterized based on the polarization curve and electrochemical impedance spectroscopy (EIS) analysis. Additionally, acidebase titrations were performed to access the phosphoric acid content in different sections of the MEAs as well as scanning electron microscopy (SEM). A low impact in the fuel cell performance was observed when three cycles of synthetic reformate containing methanol solution were performed. When the number of cycles was increased, the performance of HT-PEMFC decreases and irreversible degradation of performance was observed. The cycles with synthetic reformate increased the ohmic resistance and high frequency resistance associated with anodic processes, but decreased the intermediate frequency resistance associated with cathodic processes. Additionally, by increasing the number of cycles, the phosphoric acid content of Celtec® MEAs and the thickness of the membrane decreased.